Influência da classificação de sementes por espessura e velocidade de deslocamento na semeadura sobre a qualidade e regularidade de distribuição das sementes e produtividade do girassol - Pallaoro, Dryelle Sifuentes (2020)
The classification of seeds and the speed of sowing can affect, among other items, the regularity of the longitudinal distribution of seeds of many cultures. With regard sunflower cultivation, few studies have been developed so, the objective was to evaluate the effect of seed classification by the thickness and the speed displacement of the seeder-fertilizer on the quality of the seeds after sowing, on the uniformity of longitudinal distribution of plants and on the sunflower production components. Sunflower seeds from two cultivars were classified, separating into two groups (C1 and C2) according to their thickness, being reserved some portions of unclassified seeds (NC). After classification, biometric evaluation and sowing were performed in 5.0; 6.5; 8.0 and 9.5 km h-1 , in 2017 and in 2018, the speed of 11.0 km h -1 was added to those mentioned. Were adopted as control, the seeds that did not pass through the dosing mechanism. The collection of seeds for quality evaluation (before and after the sowing operation) was carried out by sealing the end of the pipe driven from the distribution system. The first count and germination percentage, mean time and percentage emergence in sand, vigor by the accelerated aging test and tetrazolium test were evaluated in the laboratory. The initial and final plant population, the average distance between plants, the percentage of normal, failure and multiple spacing between plants, sowing depth, precision index of normal spacing, coefficient of variation of spacing and production components were evaluated in the field. It was observed that the passage of seeds through the dosing mechanism affects the physiological quality of sunflower seeds from 9.5 km h-1 . In this case, the classification of seeds by thickness did not improve the regularity of sunflower sowing, however, larger seeds provided a higher percentage of failure spacing, while smaller seeds contributed to the increase of multiple spacing. Increasing the sowing speed reduces the percentage of normal spacing between plants and worsens the sowing precision, regardless of the classification of seeds by thickness. The seeds with less thickness (C2), sown at 6.5 and 9.5 km h-1 and not classified at 8.0 km h-1 generated the highest oil grain yields.